Análise espacial da evolução do uso e cobertura da terra na sub-bacia hidrográfica do Arroio Arenal, Santa Maria/RS - Benedetti, Ana Caroline Paim (2006)
This work investigates the dynamics of the classes of land use and cover in the hydrographic subbasin of Arroio Arenal - RS, through the representation of spacetime processes. Spatial analysis of a distinct time series among the dates of October of 1995, May of 2000 and January of 2005 through a set of multisensor images was performed. It has generated representative landscape information and related them to different socioeconomic, politic and enviromental aspects inherent to the Subbasin in question. The spatial analysis starts from the LEGAL language implemented in a Geographic Information System, which became possible the application of image processing and digital classification techniques and the generation of thematic maps, such as cartographic base and slope which have complemented the representation of scenes of the studied area. The digital classification of the satellite images was carried out in the supervised mode, using the Bhattacharya classifier algorithm. The generated data had supported the spatial analysis of the land use and cover, in which had been defined the main parameters to evaluate the dynamics of the studied area: forest evolution, agricultural evolution and regeneration evolution. Among the main results, it is highlighted the predominance of the fields in the regional landscape, occupying 63.71% of the area and the great agricultural advance on these areas, quantified at the end of the period in 8.830,163 ha and still the addition of forest areas in 6.276,749 ha. From the mapping of the Permanent Preservation Areas and the environmental conflicts caused by the agricultural practices in inadequate places, 1,719.957 ha had been delimited as priority reforestation areas. It is concluded that the intensity of the exploratory activities in the subbasin is responsible for many changes occured during the analyzed period.